Peran Pola Asuh Orang Tua dan Pembentukan Motivasi Anak dalam Pemilihan Olahraga Renang - Aliya, Rusyda Nur; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian , Geraldi (Institut Teknologi Bandung, 2024)
Parental parenting is one of the obstacles in a child's motivation to choose a sport. Parenting style is the closest thing to a child's development, so parents' parenting style will have an impact on the child's motivation. This research aims to examine the relationship between parenting styles and the formation of children's motivation in choosing the sport of swimming. By using descriptive methods and quantitative approaches. The sample in this study involved 34 people (15 women and 14 men). This research used the SIMS (The Situational Motivational Scale) and PSDQ (The Parenting Style and Dimension Questionnaire) questionnaires which were filled in by the sample using Google Form. The research results show that there is a significant relationship between the role of parental parenting and the formation of children's motivation in choosing swimming. The conclusion of this research is that parenting styles play an important role in forming children's motivation in choosing swimming, so parents are advised to pay more attention to the parenting patterns given to children to increase motivation in choosing sports, especially swimming.